Assessment of Land Degradation in Relation to Human-Induced Causes in Agro-Ecological Zones in the Merek Catchment, Iran - Heshmati, Mosayeb (2010)
Land degradation is the loss in the productivity of land resources due to many factors, especially soil erosion. Nutrient depletion and soil organic carbon (SOC) loss are the main impacts of erosion which not only cause declining crop yields, but also induce off-site impacts, such as eutrophication and greenhouse gas (GHG) emission. The objectives of this study were to identify land degradation factors through studying the physico-chemical and mineralogical properties of soil and rocks as well as human-induced factors within agro-ecological zones and estimate the erosion rate and loss of plant nutrients (N, P, K and SOC) for integrated management of the degraded areas. The study was conducted at the Merek catchment, Iran which is geologically characterized by limestone, sandstone, shale and marls in order to determine the factors responsible for land degradation. In this study, geomorphological facies within the three agro-ecological zones in the catchment were mapped by overlapping geological, topographical, land use and erosion data using satellite image and geographical information system (GIS). Rock and soil samples were randomly sampled within each facies to determine their physico-chemical and mineralogical properties. The erosion rate and loss of plant nutrients (N, P and K) and SOC were estimated using modified pacific southwest inter agency committee (MPSIAC) model. The erosion rates in the agriculture area, rangeland and forest were 10.61, 11.02 and 13.05 t ha-1yr-1, respectively. The respective predicted annual N depletion by erosion were 15.16, 18.73 and 23.75 kg ha-1yr-1 in agriculture area, rangeland and forest zone, while that of P were 0.172, 0.170 and 0.165 kg ha-1yr-1. The depletion of K in the agriculture area, rangeland and forest were 4.47, 4.65 and 5.15 kg ha-1yr-1, respectively. The highest loss in SOC was in the forest with a value of 306.10 kg ha-1yr-1, while the lowest was in the agriculture area at 147.23 kg ha-1yr-1. The high loss of SOC in the forest zone is due to serious soil erosion, which is accelerated by sloping land. Part of the study area is geologically and topographically susceptible to landslide. This area mainly comprises unstable soils that tend to promote incidence of landslide. The study found that landslide has affected about 15% of the catchment and that its occurrence was promoted by unstable soils, being eroded at the rate of 13.07 t ha-1yr-1. Field observations showed that the landslide was initiated by crack formation in areas having smectite, a mineral which can swell and crack, depending on the availability of water. Smectite is the dominant mineral in about 80% of the area affected by landslides. Low aggregate stability in the topsoil further promotes the occurrence of landslides. Most of the landslides occurring in the forest areas were observed where the canopy cover was less than 15% with slope of 10-40%. Social issues such as low income, poverty and low level of welfare and education contribute to land degradation in the study area. Subsequently, farmers, herders and nomads were interviewed and relevant experts were consulted. The results revealed that improper tillage practices, overgrazing and forest clearance were the worst significant human-induced factors causing land degradation. The other factors include crop cultivation without rotation and fallow period, improper tillage practices, crop residue burning and conversion of rangelands and forest to agricultural lands. Training and extension, soil conservation measures with farmer’s participation, enactment of new laws and amending of current laws (for monitoring agricultural activities such as fertilizers and pesticide application and burning of crop residues), forest preservation, improving the current grazing systems and empowering government employees are the possible measures to curtail land degradation in the study area. It is suggested that the government should create job opportunities among the unemployed in the village and enhance their welfare by introducing insurance, health services and educational opportunities.